2007
DOI: 10.1371/journal.pgen.0030011
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Code for Transcriptional Response Diversity and Its Relation to Genome Structural Properties in A. thaliana

Abstract: Regulation of gene expression via specific cis-regulatory promoter elements has evolved in cellular organisms as a major adaptive mechanism to respond to environmental change. Assuming a simple model of transcriptional regulation, genes that are differentially expressed in response to a large number of different external stimuli should harbor more distinct regulatory elements in their upstream regions than do genes that only respond to few environmental challenges. We tested this hypothesis in Arabidopsis thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 59 publications
7
105
0
Order By: Relevance
“…2D and SI Appendix, Table S10). A small possibility exists that these data support a previously reported suggestion that RNA expression is less variable and often tissue specific for long CDS (40)(41)(42), which might lead to more consistent protein expression. However, a more likely explanation for our results is that low-molecularweight proteins are sampled less frequently in GeLC-MS/MS experiments (43), and these proteins thus seem to be poorly correlated with transcript levels in our binary comparisons.…”
Section: Root Cellular Proteome Reveals Cellular Functions and Spatialsupporting
confidence: 87%
“…2D and SI Appendix, Table S10). A small possibility exists that these data support a previously reported suggestion that RNA expression is less variable and often tissue specific for long CDS (40)(41)(42), which might lead to more consistent protein expression. However, a more likely explanation for our results is that low-molecularweight proteins are sampled less frequently in GeLC-MS/MS experiments (43), and these proteins thus seem to be poorly correlated with transcript levels in our binary comparisons.…”
Section: Root Cellular Proteome Reveals Cellular Functions and Spatialsupporting
confidence: 87%
“…cis-Acting regulatory elements and their corresponding transcription factors constitute one of the transcriptional regulatory mechanisms induced by different environmental and extracellular conditions to help the plants in adaptive strategies (52). Therefore, the presence of numerous putative cis-regulatory motifs in the three OSC promoters suggests control over their transcriptional activity being mediated in response to various signals.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional initiation requires assembly of this polymerase to a core promoter structure such as the TATA box which is present in about 20% of Saccharomyces cerevisiae genes (Basehoar et al 2004). Remarkably, TATA-containing genes seem to be enriched in stress response genes, a notion that applies to plants (Walther et al 2007) and humans (Yang et al 2007), and suggests that TATA motifs are associated with rapid and variable regulation. Indeed, it was shown that stress-related proteins expressed from genes with a TATA box exhibit a high level of intrinsic variability (Newman et al 2006).…”
Section: Stress-induced Transcription and The Tata Boxmentioning
confidence: 99%